Fashion Sebagai Perlawanan dan Media Komunikasi - Maradita Sutantio (JURNAL RUPA, 2020)
This article examines the function of clothing and fashion products, which not only serve as a means of body protection - they can also be a means of communication and resistance. Fashion symbolically constructs collective myth which describe a marker of situations in various eras. This includes the emergence of the phenomenon of slow fashion and sustainable fashion which emerge as a form of resistance to the fast fashion wave in the fashion world. This system emerged from developed countries from America, England, Europe and Australia with standards arranged in a circular system. Sustainable fashion is considered a solution to the imbalance of the fashion product industry system. In the collective cultural awareness, fashion uses language and special markers outside of its main function as body armor, fashion also constructs signs within the wearer as an entity capable of communicating as a whole. Thus, it is identified as an independent and single product which is associated with its own meaning. Using Roland Barthes’s theory, this article shows fashion consists of language making and consumer expressions in the guise of consumerism, materialism, commercialism, and the marketing wave of fashion, so that we hardly realise that we have put primordial human things aside.